THE USE OF SOLAR DRYERS IN THE DEVELOPMENT OF TECHNICAL CREATIVITY OF STUDENTS IN PHYSICS LESSONS - Khamdamova Nozima Muqimovna (Journals Park Publishing, 2022)
This article provides a systematic analysis of the use of alternative energy sources in various sectors of the economy in the development of technical creative competencies of students in physics and extracurricular activities. In the education system, the pedagogical possibilities of technical thinking in the development of technical creative competencies of students, the design, construction and modeling of models and models of various devices used in production are studied. Innovative educational technology, creative technology, brainstorming, development of recommendations for improvement with the help of modern tools, pedagogical based on.
Keywords: devices of alternative energy sources, technical creativity, competence, design, physics